2010
DOI: 10.1051/radiopro/2010001
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of U(nat),226Ra,230Th and210Po in vegetables by adult inhabitants of Bagjata uranium mining area, Jharkhand, India

Abstract: Ingestion of radionuclides through food intake accounts for a substantial part of radiation doses and vegetables constitute essential components of the diet, by contributing protein, vitamins, iron, calcium and other nutrients. Radionuclides can be apprehended in the ecosystem of the East Singhbhum region which is known for its viable grades of uranium. In the present study, vegetables were collected from the villages around the proposed Bagjata mining area and analysed for U(nat), 226

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Variations in the values of the ELCR due to ingestion of fruits are due to the different conversion factors for different age category. This is in agreement with Priharti, et al [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Also the internal hazard index for all the fruits from different states in Niger Delta showed that the internal hazard due to Apricot is very high.…”
Section: Discussionsupporting
confidence: 86%
“…Variations in the values of the ELCR due to ingestion of fruits are due to the different conversion factors for different age category. This is in agreement with Priharti, et al [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Also the internal hazard index for all the fruits from different states in Niger Delta showed that the internal hazard due to Apricot is very high.…”
Section: Discussionsupporting
confidence: 86%
“…Usually, the US-EPA considers cancer risks that are bellow 1 × 10 -6 , to be so small as to be negligible and risks above 1 × 10 -4 to be adequately large that some sort of remediation is desirable. Cancer risks that range between 1 × 10 -6 and 1 × 10 -4 are generally considered to be acceptable [ 56 , 57 ]. Therefore, from the calculated values obtained in this study, the seafood-consuming populace may be at considerable risk.…”
Section: Discussionmentioning
confidence: 99%
“…Based on highlights of the study Hakonson-Hayes et al [92], Giri et al [93] and Hashim & Najam [94], it was found that the main way people are exposed to U toxicological and radiological ill-effects is by directly drinking contaminated groundwater, accounting for more than 85-99% of the health risks for human consumers. Considering established safety measures and relying on oral ingestion, the World Health Organization (WHO) has set a Tolerable Daily Intake (TDI) of 0.6 µg/kg body weight per day for soluble U [95].…”
Section: Occurrence Of Uranium In Soil-plant Systemmentioning
confidence: 99%